The use of Geographic Information Systems as innovative tools for sustainable development strategies and enhancing the efficiency of forest sector entities - Lutsiv Nataliia; Pavlo Chukhna (Наукові праці Лісівничої академії наук України)
The article examines the ways of using the potential of Geographic Information Systems (GIS) for integrating ecological and economic parameters of forest use into forest management processes. The research methodology was based on the analysis of scientific publications on the application of GIS in forest management and comparison of various forest management practices.